Varejo multicanal: grau de integração e o varejo de livros no Brasil - Porto, Roseli Morena (2006)
Upon a decade of business Internet in Brazil is celebrated, specialists are unanimous to state that it did not only come for good but it has chiefly led many businesses to adopt new channels, industries to rethink their focuses, having introduced them to new ways of assisting their customers, besides having prompted changes in management, operations, and development of their strategies. Such a context serves as basis to outline this study’s main purpose, which is to investigate the integration phenomenon in the multichannel retail trade of Brazilian companies focused on the bookstore business. Multichannel retail means the companies’ know-how of making available to their customers more than one channel for them to shop, with physical stores and business sites in Web environment being prominent. This research's particular purpose is to understand the studied companies’ goals when adopting the multichannel retail technique if compared to the expansion strategy, how the already existing competitive advantages were leveraged with the integration of virtual stores, which is the degree of activities integration in both physical and virtual environments as regards management, operations, and measurement, as well as concerning variables of “The Six P’s of the Retail Mix” endeavoring to ascertain how they are found in the different stages of integration. For such purpose, the theoretical reference tried to add to the Multichannel Retail concept the elements of the already established concepts of Growth Strategy, Strategic Business Unit (SBUs), and Synergy. This qualitative research was carried out with three bookstore chains with strong nationwide presence. The results found show that the surveyed companies managed to expand their businesses and leverage their competitive advantages, integrating distinctively the management, operations, and measurement, as well as the variables of their retail-trade compound, placing them in different stages of integration of both their physical and virtual channels.